The law on sport in the light of the opinion of the fitness instructors and personal trainers - Patrycja Proskura; Kazimierz Witkowski (Kazimierz Wielki University, 2017)
The popularity of the work as a fitness instructor and personal trainer in our country continues to grow. Right about this flu in Poland is not regulated, which creates a lot of concerns about the quality of their qualifications. The existing law on sport of 25 June 2010 requirements for trainers  and  instructors, excluded the requirement of graduate and cut off the procedure of applying for consent to the competent Minister of physical culture to carry out specialized trainer courses and instructor. The aim of the article was to examine the experience of the same fitness instructors and personal trainers on the current law on sport. The research was conducted in various fitness clubs, involving 100 respondents.